Juhūd al-Marʼah wa Dawruhā fī Riwāyat al-Ḥadīth - Umma Farida (Al-Zahra : Journal for Islamic and Arabic Studies, 2005)
In the history of Islamic scholar, men dominated the process of most Hadith narration from the Prophet Muhammad PBUH. However, the role of women in these fields cannot be underestimated. This is seen clearly, when they asked the Prophet to assigned a day to teach them and asked questions related to their lives without embarrassment. They possessed lots of knowledge with regard to worship and muamalat. In fact, they thoroughly pay attention with the words of the Prophet. Among the shahābiyāt, some become critics of Hadith, like Aisyah, the wife’s of the Prophet.